2012
DOI: 10.1590/s1516-89132012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the shelf-life of vegetable-type soybean pods

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…During postharvest storage, concentration and pattern of free amino acids are very sensitive to the changes occurring in immature vegetable soya beans because of increased activities of metabolic enzymes such as protease. Although several studies had mainly implicated on the storage period of postharvest vegetable soya beans through evaluating chemical and physical characteristics of pods (Czaikoski et al ., ; Santana et al ., ), the research related to systematically investigating the dynamic changes of free amino acids in immature vegetable soya bean is still precarious. Elucidation of changes of these components during storage will represent an important step towards an understanding of the basic processes related to immature soya bean taste and quality loss after harvest.…”
Section: Introductionmentioning
confidence: 99%
“…During postharvest storage, concentration and pattern of free amino acids are very sensitive to the changes occurring in immature vegetable soya beans because of increased activities of metabolic enzymes such as protease. Although several studies had mainly implicated on the storage period of postharvest vegetable soya beans through evaluating chemical and physical characteristics of pods (Czaikoski et al ., ; Santana et al ., ), the research related to systematically investigating the dynamic changes of free amino acids in immature vegetable soya bean is still precarious. Elucidation of changes of these components during storage will represent an important step towards an understanding of the basic processes related to immature soya bean taste and quality loss after harvest.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method to increase the shelf-life of vegetable-type soybeans grains would be canning. Santana et al (2011) observed that to preserve the quality of vegetabletype soybean grains, pods should be stored at 30ºC and consumed within 24 hours or stored in closed plastic bags at 7ºC and consumed within 3 days; these conditions guarantee the maintenance of protein content, sweetness and color.…”
Section: Resultsmentioning
confidence: 99%
“…Then the soya bean pods were stored in micro‐perforated (hole diameter 0.5 mm) polyethylene bags (500 g per bag) at an outside temperature of 1 ± 1 °C and a relative humidity (RH) of 85–95% in darkness, bags had a thickness of 0.04 mm and micro‐perforations spacing of approximately 2 mm. The shelf life was then determined according to the previous report (Santana et al ., ) and defined as the time for quality to decline to 30% yellowing in pods. The optimal spermine concentration was used for further study.…”
Section: Methodsmentioning
confidence: 99%